2019
DOI: 10.1016/j.scitotenv.2018.08.364
|View full text |Cite
|
Sign up to set email alerts
|

Leaching behavior of major and trace elements from sludge deposits of a French vertical flow constructed wetland

Abstract: Surface sludge deposits were collected from a French Vertical Flow Constructed Wetland (French VFCW) sewage treatment plant. The objectives were to characterize the retention of major elements and trace metals within the sludge deposits particles under regular operating conditions, and the influence of extreme pH conditions on their potential release which may occur in situations when the plant malfunctions or after land application of the dredged sludge. A sequential extraction protocol was first used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…(2006), Levlin (2005) and Kania et al . (2019). This result was not unexpected; phosphorus in the sewage sludge ash is mostly present in bonded forms with metals and can be dissolved completely in acidic conditions according to Eqs (); however, only Al‐P is directly leachable via alkaline dissolution (Eq. )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2006), Levlin (2005) and Kania et al . (2019). This result was not unexpected; phosphorus in the sewage sludge ash is mostly present in bonded forms with metals and can be dissolved completely in acidic conditions according to Eqs (); however, only Al‐P is directly leachable via alkaline dissolution (Eq. )…”
Section: Resultsmentioning
confidence: 99%
“…Plus, whereas Kania et al . (2019) achieved higher phosphorus dissolution under acidic condition, release efficiency was higher during alkaline leaching in the study of Kim et al . (2016) and it is proposed that, higher efficiency of alkaline condition might have been caused by the lower alkaline buffer capacity of the sludge.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The study showed those wetlands in operation one year or less had more abundant organic matter, less humified, and more biodegradable than more established wetlands (three years of operation or more) (Kania, Gautier, Imig, et al, 2019). To assess the ability of the sludge to retain specific elements including trace metals under both normal operating conditions and extreme pH conditions, samples from the wetlands noted above were examined for leaching (Kania, Gautier, Blanc, et al, 2019). The sludge layer properties, in particular permeability, were examined for their potential influence on hydraulic behavior in gravel‐based vertical flow constructed wetlands indicating increased organic matter improved permeability by three times, while total solids increase reduced permeability; improvements in mineralization related to drying kinetics was also described (Khomenko, Dotro, Jefferson, Coulon, & Bajon Fernandez, 2019).…”
Section: Sludge To Biosolids: Treatment Advancesmentioning
confidence: 99%
“…Then, pH and element release are monitored and reported as a function of the amount of acidity or alkalinity. Such experiments were used to assess element release from several types of cement and concrete matrices [20,27] into contaminated soils [28], including even natural soils [29]. Several protocols were developed for these titration experiments [30], but the main principles remain the same.…”
Section: Introductionmentioning
confidence: 99%